Pengaruh Debt to Equity Ratio, Total Asset Turnover, Inflasi dan BI Rate terhadap Return Saham - Vitri Hanivah; Indra Wijaya (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
The purpose of this study was to analyze the influence of the Debt to Equity Ratio, the Total Asset Turnover, the Inflation and the BI Rate to the Stock Returns. This research was conducted using secondary data. The population in this study was the Food and Beverage industries listed on the Indonesian Stock Exchange period 2011-2015, with the total of 14 companies. The sample in this study was taken by purposive sampling method, with the total of 9 companies. This study used multiple linear regression analysis to measure the influence of independent variables on the dependent variable. The results showed that the Inflation and the BI rate had significant effects on the Stock Returns.